Pesticide Application Best Management Practices for the Citrus Grove Worker - Brian Boman; Darren Cole; Steve Futch; Ward Gunter; Jack Hebb; P. Chris Wilson (EDIS)
Revised! AE247, a 15-page fact sheet by Brian Boman, Darren Cole, Steve Futch, Ward Gunter, Jack Hebb, and Chris Wilson, is part of the Best Management Practices (BMPs) for Citrus Grove Workers series. It provides information for citrus grove workers about pests, pest control methods, pesticide toxicity, how to transport pesticides, first aid and decontamination, preventing exposure, worker protection standard, storage and disposal, pre-operation checkpoints, mixing and loading, container management, calibration, and application best management practices. Includes three quizzes and references. Published by the UF Department of Agricultural and Biological Engineering, April 2009.